2017
DOI: 10.1039/c7sc00195a
|View full text |Cite
|
Sign up to set email alerts
|

A convergent synthesis of 1,3,4-oxadiazoles from acyl hydrazides under semiaqueous conditions

Abstract: An innovative new synthesis approach to disubstituted 1,3,4-oxadiazoles is described, inspired by Umpolung Amide Synthesis (UmAS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…14 Aside from their attractive features for drug development, 17 innovative new uses for oxadiazoles continue to emerge, as do methods for their synthesis. 18 A complement of experiments in the oxadiazole synthesis revealed that the expected diacyl hydrazide was not an intermediate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Aside from their attractive features for drug development, 17 innovative new uses for oxadiazoles continue to emerge, as do methods for their synthesis. 18 A complement of experiments in the oxadiazole synthesis revealed that the expected diacyl hydrazide was not an intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…In this reaction, controlling the generation rate for the iodonium species by slow addition of UHP is crucial to achieve good yields, presumably to limit acyl hydrazide overoxidation, a process that would draw the electrophilic acyl diazene intermediate away from productive reaction with an α-bromo nitroalkane. 14,15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tokumaru et al [55] in 2017 found new approach to prepare 1,3,4-oxadiazoles. They reported new method to deliver the 2,5-disubstituted oxadiazole directly, avoiding 1,2-diacyl hydrazide intermediate by coupling α-bromo nitroalkanes with acyl hydrazides.…”
Section: Synthesis Of 134-oxadiazoles From Acyl Hydrazidesmentioning
confidence: 99%
“…On the contrary, oxadiazoles are deployed as bioisostere for ester, ketone, carbamate and amide functionalities ,. While exploiting with their modulation at 2‐ and 5‐postions, they are valued for divergent physicochemical and pharmacokinetic profiles . Favorable ADME properties and metabolic stability against peptidase and hydrolytic esterase enzymes make oxadiazole as an essential pharmacophore .…”
Section: Introductionmentioning
confidence: 99%